Comparison Study of Four Typical ORC Configurations for Different Waste Heat Characteristics of Engine. (13th March 2023) - Tian, Hua; He, Zhaoxian; Zhang, Xuanang; Li, Ligeng; Cai, Jinwen; Wang, Xuan; Liang, Xingyu; Shu, Gequn
Abstract : The organic Rankine cycle (ORC), as the most promising technology for engine waste heat recovery, has many configurations available to match the complicated engine waste heat conditions. This paper is aimed at revealing the characteristics of the engine waste heat condition for which different ORC configurations are matched so as to give selection guidance. The engine waste heat sources are characterized by the exhaust gas temperature (300°C-650°C) and the heat ratio of the high temperature waste heat to low temperature waste heat (0.5-1.5). Four mostly investigated configurations including the single-loop ORC, the cascade dual-loop ORC, the dual-pressure ORC, and the CO2 transcritical Rankine cycle (CTRC) are selected and modified to enable efficient utilization of all waste heat sources. Their thermodynamic performance is optimized for different waste heat characteristics. The results show improvements in net power for all configurations when exhaust gas temperature and heat ratio rise from 300°C, 0.5, to 650°C, 1.5, respectively, of which the high-temperature split CTRC (HTS-CTRC) recorded the largest increase of 183.58%, while the split regenerative ORC (SR-ORC), dual-pressure ORC (D-ORC), and split cascade ORC (SC-ORC) increased by 17.41%, 23.71%, and 35.45%, respectively. Two selection maps are established to provide general references for quickly selecting the configuration according to different waste heat characteristics whatever the engine type and operating conditions.